Placenta Imaging Workshop 2018 report: Multiscale and multimodal approaches. (April 2019) - ,; Atkinson, David; Aughwane, Rosalind; Baranikumar, Rupanjali; Bertholdt, Charline; Bonet-Carne, Elisenda; Brownbill, Paul; Brownbill, Paul; Bruchhage, Muriel; Caulfield, Richard; Chernyavsky, Igor; Chew, Andrew; et al.
Abstract: The Centre for Medical Image Computing (CMIC) at University College London (UCL) hosted a two-day workshop on placenta imaging on April 12th and 13th 2018. The workshop consisted of 10 invited talks, 3 contributed talks, a poster session, a public interaction session and a panel discussion about the future direction of placental imaging. With approximately 50 placental researchers in attendance, the workshop was a platform for engineers, clinicians and medical experts in the field to network and exchange ideas. Attendees had the chance to explore over 20 posters with subjects ranging from the movement of blood within the placenta to the efficient segmentation of fetal MRI using deep learning tools. UCL public engagement specialists also presented a poster, encouraging attendees to learn more about how to engage patients and the public with their research, creating spaces for mutual learning and dialogue. Highlights: Summary of the Centre for Medical Image Computing Placenta Imaging Workshop 2018. Talks covered multiscale and multimodal imaging techniques. Panel discussion on the future of placental imaging research. Discussion of placenta-specific public engagement issues.